BENGKAYANG STUDENTS’ STRATEGIES TO IMPROVE THEIR PRONUNCIATION - Elvin, Mark; Listyani, Listyani - (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2024)
Pronunciation is one of the main keys in mastering speaking English. Without correct pronunciation in speaking English, EFL students can not communicate well and it will be hard for others to understand what they are saying. The study aimed to find out the strategies that English Language Education Program students from Bengkayang used to improve their pronunciation skills at the Faculty of Language and Arts in Universitas Kristen Satya Wacana, Salatiga. The participants of the study were twenty-one (21) students from batch 2019 who had taken the Pronunciation Practice class in Semester 1 of the 2021/2022 academic year. This study was conducted to answer one research question: What are Bengkayang students' strategies to improve their pronunciation skills? The participants were chosen randomly to be the participants because they were all from Bengkayang, a province in Kalimantan Barat, Indonesia. They had various ways of pronouncing words. The researcher used a set of questionnaire questions consisting of close-ended and open-ended questions. Semi-structured interview questions were also used to collect the data from the students. The findings showed that the strategies used by the students were watching online video(s), listening to songs in English, practicing with friends, and using an online application (ELSA). The students were familiar with the strategies used because those strategies were suggested by the teachers in the classroom. The students chose the strategies differently because they came from different places and each place has different strategies to use. Eventually, this study hopefully provides information for teachers or other students outside Bengkayang who face similar problems.